(untitled) (Journal Intellectual Sufism Research (JISR), 2019)
The purpose of this research was to analyze the difference in self control students student boarding schools of Jagad ’alimussirry with the students in the UNESA. This research is both a quantitative approach to the field (field research). Determination of the sample in this research was conducted with a purposive sampling technique. Based on the engineering samples taken as many as 105 subject, 18 students from boarding schools of Jagad ’ alimussirry and 87 of the students from several departments. Data collection was done through the dissemination of the scale. The data analysis used the t-test is a test that is independent sample test with the help of SPSS (Statistical Product and Service Solution) 23.0 version for windows. The results can be seen from the results of a test of the hypothesis gained 0.106 significance so (p > 0.05). This result shows that shows that Ho is accepted which means no difference a change or an increase in the average value of self control was significant between a group of students and students from various PPJA majoring in UNESA.